Letters to a Painter on the Theory and Practice of Painting - Ostwald, Wilhelm (Ginn and Company, 1907)
Volume inspired by correspondence between Wilhelm Ostwald (1853-1932) and various contemporary artists. According to Ostwald, "These letters appeared during the winter and spring of 1903-1904 in the scientific supplement of the Münchener Allgemeine Zeitung.... and from these letters in part came the idea of this expansion into book form." Contains seventeen chapters primarily concerned with the physicochemical aspects of painting media and technique. Ostwald was a German chemist and philosopher. In 1909, he received the Nobel Prize in Chemistry for his work on catalysis and his investigations into the fundamental principles governing chemical equilibria and rates of reaction. Ostwald is considered one of the founding fathers of physical chemistry. When he retired in 1906, Ostwald studied art, philosophy, and politics. Work is digitized in its entirety.
Keywords: Morse, Harry W. (Harry Wheeler), 1873-; Ostwald, Wilhelm, 1853-1932; Painting; Pigments; Reflection (Optics); Chemistry, Physical and theoretical